2011
DOI: 10.1007/s11095-011-0461-2
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Analysis of Low Quantities of Phase Separation in Hot-Melt-Extruded Solid Dispersions: A Combined Atomic Force Microscopy, Photothermal Fourier-Transform Infrared Microspectroscopy, and Localised Thermal Analysis Approach

Abstract: We have demonstrated that the novel combined approach allows site-specific characterisation of the extruded systems and that drug distribution may be uneven across the extrudates, with concomitant implications for understanding stability and drug release behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 35 publications
(70 reference statements)
1
49
0
Order By: Relevance
“…Step changes in the reversing heat flow indicate the presence of a (putative) glass transition upon heating and the midpoints of the glass transition were observed at 126.1°C for CsA and 51.4°C for Eudragit EPO. These values are in good agreement with literature values (7, 9, 29) and indicate that both materials are in an amorphous form before processing by HME. However it should be emphasized that there is some uncertainty regarding the thermophysical behavior of CsA in that while some sources have attributed the heat capacity change to a glass transition (29), others have suggested that this material is liquid crystalline in nature (30).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Step changes in the reversing heat flow indicate the presence of a (putative) glass transition upon heating and the midpoints of the glass transition were observed at 126.1°C for CsA and 51.4°C for Eudragit EPO. These values are in good agreement with literature values (7, 9, 29) and indicate that both materials are in an amorphous form before processing by HME. However it should be emphasized that there is some uncertainty regarding the thermophysical behavior of CsA in that while some sources have attributed the heat capacity change to a glass transition (29), others have suggested that this material is liquid crystalline in nature (30).…”
Section: Resultssupporting
confidence: 92%
“…The commonly perceived ideal structure of such systems is a molecular dispersion, as theoretically such a structure ensures an homogenous drug distribution but also predicates that the drug is in a dissolved molecular state with no lattice energy to overcome prior to dissolution. However, such dispersions are well known to phase separate into either amorphous or crystalline drug regions and a number of studies have been conducted to facilitate prediction of such instability, including thermodynamic (solubility parameter, entropic and Flory-Huggins miscibility approaches (5, 6) and phenomenological approaches using thermal, spectroscopic and imaging methods (7). It has also been suggested that phase separation may manifest as conjugate mixes of drug and polymer rather than regions of pure material (8).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lauer et al have used AFM to characterize the homogeneity of drug-polymer mixtures prepared using a microhot melt extruder (16) and compared the data to dispersions prepared using a screening method involving solvent casting. Qi and Craig have utilized AFM coupled with local thermal analysis as well as photothermal Fourier-transform infrared (PT-FTIR) microspectroscopy to characterize their drug-loaded hot melt extrudates (25). These studies, among others, and our report herein demonstrate the power of AFM and related techniques to characterize the effect of processing and composition on the resulting phase behavior of hot melt extrudate for pharmaceutical applications.…”
Section: Discussionmentioning
confidence: 64%
“…The amorphous FD peak was notably broadened and moderately shifted to 1645.90 cm −1 . Together with the broadening and redshift of the bonded N-H group from 3371.50 to 3334.93 cm −1 (data not shown), the interactions between C=O and N-H groups of FD molecules in the amorphous state are suggested to be stronger than that in the crystalline form (46,47). In the 10 wt% FD-EPO SD standard, this carbonyl peak exhibited a further blue shift to 1649.36 cm −1 , implying a possible bonding between heterogeneous FD and EPO molecules.…”
Section: Raman Analysis and Mappingmentioning
confidence: 92%